Individual Variability in Recalibrating to Spectrally Shifted Speech: Implications for Cochlear Implants. Issue 5 (1st September 2021) - Smith, Michael L.; Winn, Matthew B.
Abstract : Objectives: Cochlear implant (CI) recipients are at a severe disadvantage compared with normal-hearing listeners in distinguishing consonants that differ by place of articulation because the key relevant spectral differences are degraded by the implant. One component of that degradation is the upward shifting of spectral energy that occurs with a shallow insertion depth of a CI. The present study aimed to systematically measure the effects of spectral shifting on word recognition and phoneme categorization by specifically controlling the amount of shifting and using stimuli whose identification specifically depends on perceiving frequency cues. We hypothesized that listeners would be biased toward perceiving phonemes that contain higher-frequency components because of the upward frequency shift and that intelligibility would decrease as spectral shifting increased. Design: Normal-hearing listeners (n = 15) heard sine wave-vocoded speech with simulated upward frequency shifts of 0, 2, 4, and 6 mm of cochlear space to simulate shallow CI insertion depth. Stimuli included monosyllabic words and /b/-/d/ and /∫/-/s/ continua that varied systematically by formant frequency transitions or frication noise spectral peaks, respectively. Recalibration to spectral shifting was operationally defined as shifting perceptual acoustic-phonetic mapping commensurate with the spectral shift. In other words, adjusting frequency expectations for both phonemes upward so that there is still a perceptual distinction, rather than hearing all upward-shifted phonemes as the higher-frequency member of the pair. Results: For moderate amounts of spectral shifting, group data suggested a general "halfway" recalibration to spectral shifting, but individual data suggested a notably different conclusion: half of the listeners were able to recalibrate fully, while the other halves of the listeners were utterly unable to categorize shifted speech with any reliability. There were no participants who demonstrated a pattern intermediate to these two extremes. Intelligibility of words decreased with greater amounts of spectral shifting, also showing loose clusters of better- and poorer-performing listeners. Phonetic analysis of word errors revealed certain cues were more susceptible to being compromised due to a frequency shift (place and manner of articulation), while voicing was robust to spectral shifting. Conclusions: Shifting the frequency spectrum of speech has systematic effects that are in line with known properties of speech acoustics, but the ensuing difficulties cannot be predicted based on tonotopic mismatch alone. Difficulties are subject to substantial individual differences in the capacity to adjust acoustic-phonetic mapping. These results help to explain why speech recognition in CI listeners cannot be fully predicted by peripheral factors like electrode placement and spectral resolution; even among listeners with functionally equivalent auditory input, there is an additional factor of simply being able or unable to flexibly adjust acoustic-phonetic mapping. This individual variability could motivate precise treatment approaches guided by an individual's relative reliance on wideband frequency representation (even if it is mismatched) or limited frequency coverage whose tonotopy is preserved.